Makna Relief Pura Dalěm Kělod Sangsit Sebagai Media Pembelajaran Teologi Hindu - Putra, I Wayan Sunampan; Ni Made, Yunitha Asri Diantary; Windya, Ida Made (Kamaya: Jurnal Ilmu Agama, 2024)
Pura Dalěm Kělod Sangsit is a unique temple. The unique thing is that it is found in the reliefs carved on the walls of the Dalěm Kělod Sangsit Temple. Another interesting thing is the depiction of sexuality or scenes of sexual intercourse. The uniqueness there is different from the concept of holy places in general. Due to these problems, this research aims to explore the meaning of the reliefs of the Dalěm Kělod Sangsit Temple. The method is a qualitative approach taking the location in Sangsit Village, Sawan District, Buleleng Regency. The results of this research are; The reliefs of Pura Dalěm Kělod Sangsit provide various meanings. The meaning of Pura Dalěm Kělod Sangsit related to the Hindu Theology Study program is; a) Meaning of Hindu Theology; Pura Dalěm Kělod Sangsit as a worship of Lord Śiwa. Even in the reliefs at Pura Dalěm Kělod Sangsit, various manifestations of God are depicted as symbols of Hindu theology. b) The meaning of Exchatology can be seen from the appearance of the reliefs at Pura Dalěm Kělod Sangsit which depict human life when entering the world of spirits or the world of death. c) The didactic meaning can be seen from the existence of the reliefs at Pura Dalěm Kělod Sangsit which depict the teachings of karma phala. Karma phala is the concept of cause and effect. The appearance on the relief of Pura Dalěm Kělod Sangsit tells about the punishment for spirits who commit sins in the afterlife. Based on the meaning of the reliefs at Pura Dalěm Kělod Sangsit, it can be concluded that the reliefs of Pura Dalěm Kělod Sangsit have a deep meaning. Hence, they are relevant as a learning medium in the Hindu Theology Study Program.